A methyl-to-acetyl switch in H3K27 drives metabolic reprogramming and resistance to BRAFV600E inhibition in melanoma - Jiang Zhou; Xinxin Chai; Yi Zhu; Zhi Huang; Tingting Lin; Zhen Hu; Guangdi Chen; Chi Luo; Rutao Cui; Jinghao Sheng (Neoplasia: An International Journal for Oncology Research)
The BRAFV600E pathway and epigenetic machinery are central to melanoma pathogenesis. However, how these processes intersect and their potential for synthetic lethality remains unclear. Here, we identified a BRAFV600E-driven epigenetic mechanism in melanoma that involves a H3K27 methylation-to-acetylation switch, facilitating metabolic adaptation to targeted therapies. Inhibition of BRAFV600E downregulates the methyltransferase EZH2, leading to KDM6A-mediated removal of H3K27me3 and a subsequent increase in H3K27 acetylation (H3K27ac). This H3K27 methyl-to-acetyl conversion shifts chromatin from a repressive to an active state, thereby promoting gene transcription through the acetylation reader BRD4. Specifically, the KDM6A-H3K27ac-BRD4 axis upregulates PGC1α, a master regulator of mitochondrial metabolism, enabling melanoma cells to sustain oxidative metabolism and survive BRAFV600E-targeted therapies. Blocking this H3K27 methyl-to-acetyl switch disrupted metabolic adaptation and sensitized melanoma cells to BRAFV600E inhibition. In conclusion, we revealed an epigenetic and metabolic reprogramming mechanism that enables melanoma to survive the treatment with BRAFV600E inhibitors, presenting druggable targets within the H3K27 modification pathway that could enhance the efficacy of BRAF-targeted therapies in melanoma patients.